el art. 47.1 del codigo de trabajo en actual vigencia y que se refiere a la nueva jornada de trabajo, vulnera los derechos del trabajor en general - Ayala Villacrés, Cristian Santiago (2016)
Our Constitution of the Republic stable that workers' rights are inalienable and intangible, that is, under no circumstances may be restricted or diminished in its application; From this perspective we can see that the latest labor reforms have not been addressed in this regard and contrary allow labor flexibility, which undoubtedly affects the rights of workers. On March 28, 2016 was promulgated in Official Gazette ORGANIC LAW FOR THE PROMOTION OF YOUTH WORK, UNIQUE SETTING THE DAY OF WORK, UNEMPLOYMENT AND UNEMPLOYMENT, this law among other things, allows flexibility in working hours, or whether it can reduce the daily work of mutual agreement between employer and worker. This reduction of the working day implies that the worker's remuneration will decrease as it will cancel only for hours worked, and shorter working hours, less pay for the worker; here it focuses the main idea of my thesis. Has analyzed what Art. 47.1 of the Code of work I could clearly determine that this legal provision undermines workers' rights and violates their rights fully recognized in the Constitution of the Republic and international treaties ratified by Ecuador. Since we can realize the current legislation is not fully guaranteeing the rights of workers as having less income the worker, this will directly affect the economy of the family and therefore their quality of life, and that as I said earlier breach any constitutional precept, why it is important that the legal provision invoked before in order to safeguard the interests of workers in general be repealed.